Islamic Values and Da'wah-Based Human Resource Development Strategy Through Syarifuddin Outbound And Leadership Development (SOLID) - Pramuja, Alvin Dian; Khuzaini; Kartika MR, Galuh Nashrulloh (Institut Agama Islam Syarifuddin Lumajang, 2024)
This study aims to identify and analyze Islamic values and Da’wah-based human resource development strategies implemented by Syarifuddin Outbound and Leadership Development (SOLID) in Lumajang district. SOLID, as a human resource development organization, focuses on improving individual capacity through outbound activities, skills training, and leadership seminars, with an approach that instills Islamic moral and spiritual values. Most importantly, the existence of SOLID is also a form of Islamic propagation or preaching, which shows that Muslims are also capable of innovating in the field of human resource development. This research uses a case study method with a descriptive qualitative approach, utilizing data from in-depth interviews, observations, and documentation analysis to understand the pattern of character and skills development applied. The findings show that SOLID successfully integrates values such as honesty, responsibility, and fairness in each of its activities, which not only improves participants' technical competencies, but also shapes the character of ethical and Islamic leadership. This strategy contributes to the development of human resources who not only excel professionally but also have a solid moral foundation. The results of this study are expected to be a reference for HR development institutions that want to integrate Islamic values in their training programs.